Novel Therapies in Takayasu Arteritis - Regola, Francesca; Uzzo, Martina; Toniati, Paola; Trezzi, Barbara; Sinico, Renato Alberto; Franceschini, Franco (Frontiers in Medicine, 2022)
Takayasu Arteritis (TAK) is a large-vessel vasculitis that preferentially involves the aorta and its primary branches. Cardiac involvement is frequent in TAK and is a major determinant of the patient’s outcome. Glucocorticoids (GC) are the mainstay of therapy for TAK, with high doses of GC effective to induce remission. However, relapses are common and lead to repeated and prolonged GC treatments with high risk of related adverse events. Potential GC toxicity is a major concern, especially because patients with TAK are young and need to be treated for several years, often for the whole life. Conventional immunosuppressive drugs are used in patients with severe manifestations but present some limitations. New therapeutic approaches are needed for patients with refractory disease or contraindications to conventional therapies. Fortunately, major progress has been made in understanding TAK pathogenesis, leading to the development of targeted biotherapies. In particular, IL-6 and TNF-α pathways seems to be the most promising therapeutic targets, with emerging data on Tocilizumab and TNF inhibitors. On the other hand, new insights on JAK-Inhibitors, Rituximab, Ustekinumab and Abatacept have been explored in recent studies. This review summarizes the emerging therapies used in TAK, focusing on the most recent studies on biologics and analyzing their efficacy and safety.